A validation study of the 2003 American College of Cardiology/European Society of Cardiology and 2011 American College of Cardiology Foundation/American Heart Association risk stratification and treatment algorithms for sudden cardiac death in patients with hypertrophic cardiomyopathy. Issue 8 (22nd January 2013) - O'Mahony, Constantinos; Tome-Esteban, Maite; Lambiase, Pier D; Pantazis, Antonios; Dickie, Shaughan; McKenna, William J; Elliott, Perry M
Abstract : Aims: Sudden cardiac death (SCD) is a common mode of death in hypertrophic cardiomyopathy (HCM), but identification of patients who are at a high risk of SCD is challenging as current risk stratification guidelines have never been formally validated. The objective of this study was to assess the power of the 2003 American College of Cardiology (ACC)/European Society of Cardiology (ESC) and 2011 ACC Foundation (ACCF)/American Heart Association (AHA) SCD risk stratification algorithms to distinguish high risk patients who might be eligible for an implantable cardioverter defibrillator (ICD) from low risk individuals. Methods and results: We studied 1606 consecutively evaluated HCM patients in an observational, retrospective cohort study. Five risk factors (RF) for SCD were assessed: non-sustained ventricular tachycardia, severe left ventricular hypertrophy, family history of SCD, unexplained syncope and abnormal blood pressure response to exercise. During a follow-up period of 11 712 patient years (median 6.6 years), SCD/appropriate ICD shock occurred in 20 (3%) of 660 patients without RF (annual rate 0.45%), 31 (4.8%) of 636 patients with 1 RF (annual rate 0.65%), 27 (10.8%) of 249 patients with 2 RF (annual rate 1.3%), 7 (13.7%) of 51 patients with 3 RF (annual rate 1.9%) and 4 (40%) of 10 patients with ≥4 RF (annual rate 5.0%). The risk of SCD increased with multiple RF (2 RF: HR 2.87, p≤0.001; 3 RF: HR 4.32, p=0.001; ≥4 RF: HR 11.37, p<0.0001), but not with a single RF (HR 1.43 p=0.21). The area under time-dependent receiver operating characteristic curves (representing the probability of correctly identifying a patient at risk of SCD on the basis of RF profile) was 0.63 at 1 year and 0.64 at 5 years for the 2003 ACC/ESC algorithm and 0.61 at 1 year and 0.63 at 5 years for the 2011 ACCF/AHA algorithm. Conclusions: The risk of SCD increases with the aggregation of RF. The 2003 ACC/ESC and 2011 ACCF/AHA guidelines distinguish high from low risk individuals with limited power.